ZFPM2‐AS1 facilitates cell proliferation and migration in cutaneous malignant melanoma through modulating miR‐650/NOTCH1 signaling. Issue 2 (23rd January 2021) - Liu, Wenli; Hu, Xiaoding; Mu, Xin; Tian, Qiong; Gao, Tianyuan; Ge, Rui; Zhang, Jian
Abstract: Aberrant expression of long non‐coding RNA (lncRNA) zinc finger protein, FOG family member 2 antisense RNA 1 (ZFPM2‐AS1) has been identified in many tumors, but its role in cutaneous malignant melanoma remains largely obscure. Our present study was intended to unveil the role and potential mechanism of ZFPM2‐AS1 in cutaneous malignant melanoma. RT‐qPCR was utilized to analyze ZFPM2‐AS1 expression in cutaneous malignant melanoma cells. Cell counting kit‐8 (CCK‐8), colony formation, flow cytometry, and transwell analyses were utilized to assess ZFPM2‐AS1 function on cell proliferation, apoptosis, and migration. Luciferase reporter, RNA immunoprecipitation, and RNA‐pull down assays were applied to probe the regulatory mechanism of ZFPM2‐AS1 in cutaneous malignant melanoma cells. Up‐regulation of ZFPM2‐AS1 was discovered in cutaneous malignant melanoma cells. ZFPM2‐AS1 deletion restrained cell proliferation, migration, and elevated cell apoptosis in cutaneous malignant melanoma. ZFPM2‐AS1 regulated notch receptor 1 (NOTCH1) to activate the NOTCH pathway. ZFPM2‐AS1 acted as a competing endogenous RNA (ceRNA) to affect NOTCH1 expression via sponging miR‐650. Collectively, ZFPM2‐AS1 exerted an oncogenic role in cutaneous malignant melanoma progression via targeting miR‐650/NOTCH1 signaling. Our study might offer a novel sight for cutaneous malignant melanoma treatment.